Hypertrophic Cardiomyopathy with a Twist - Francis, W.; Alkuwari, M. E.; Mohiaddin, R.; Carr, C. S. (Indian Journal of Radiology and Imaging, 2021)
Hypertrophic cardiomyopathy is a relatively common inherited cardiac disorder, with echocardiography still being the initial imaging method for its diagnosis. Cardiac fibroma is a primary neoplasm that most commonly presents in childhood. We present a patient who was investigated for typical cardiac symptoms who went on to have cardiac magnetic resonance imaging and was found to have both of these conditions.
Keywords: hypertrophic cardiomyopathy; cardiac fibroma; fibroma